La incomunicación en la era informática: La habitación y Cuerdas de Bárbara Colio - Vargas, Margarita (Latin American Theatre Review, 2018)
This essay studies La habitación (2004) and Cuerdas (2009), two plays by Mexican writer Bárbara Colio. It examines how the proliferation of various means of communication has not improved human beings’ ability to communicate effectively. Whether depicting characters who are strangers or blood relations, Colio disputes popular theories of communication and demonstrates that proximity in fact leads to violence and that devices such as telephones, speakers, intercoms, computers, etc. do not necessarily connect people. Moreover, to underscore the sense of alienation, the characters in Cuerdas occupy what Max Augé calls “non-places,” including an airport, a plane, a taxi, and a stadium. Ultimately, like in the Theatre of the Absurd, Colio’s postmodern characters and her audiences are left with the certainty that life continues and that the only alternative is to accept the world as we know it.